Book Review: Ferreira, Marcos Alan (Ed.) 2022. Peace and Violence in Brazil: Reflections on the Roles of State, Organized Crime and Civil Society. Rethinking Peace and Conflict Studies - Murilo Motta (Revista Conjuntura Austral)
The book “Peace and Violence in Brazil: Reflections on the Roles of State, Organized Crime, and Civil Society”, edited by Marcos Alan Ferreira, provides a comprehensive analysis of the persistence and causes of violence in Brazil. It argues that social inequality, fragile state institutions, and actions by both state actors and criminal groups contribute significantly to high violence levels. The book employs a Peace Studies framework, emphasizing structural and cultural dimensions, such as the normalization of violence and social exclusion, as key to understanding this issue. Moreover, it highlights the roles of civil society, education, and institutional reforms in fostering peace. In addition, the book explores alternative strategies for reducing violence, including peace education and advocacy by non-governmental organizations. However, the analysis would benefit from incorporating an economic perspective, particularly regarding how illicit markets perpetuate violence. This addition could enhance the book’s scope, offering a fuller understanding of violence in Brazil.